Influence of schoolbag carriage on pattern changes in plantar pressure during walking among first-grade schoolchildren - Kasović, Mario; Zvonar, Martin; Gomaz, Larisa; Bolčević, Filip; Anton, Vincent (2018)
The aim of this study was to determine the influence of schoolbag carriage on pattern changes in plantar pressure during walking among schoolchildren of first grade. The sample consisted of 127 schoolchildren, 48.8% male (n = 62) and 51.2% female (n = 65), aged 6.7 (±0.5) years. The mean schoolbag weight was 4.2 kg (±0.7), which represented 16.9% (±3.9) of children’s body weight, thus exceeding the upper limit of the recommended 15% of the body weight and generally affecting their posture. The study has shown the statistically significant influence of the schoolbag on changes in plantar pressure pattern when walking in relation to walking without the schoolbag. Using a t-test for large dependent samples and by setting statistical significance at p≤.05, the significant increase was noticed in peak pressure for the forefoot (p=.000; 17.1%), midfoot (p=.000; 5.7%) and hindfoot (p=.004; 3.9%) as well as in average pressure for the midfoot (p=.005; 6.2%). Also, due to the compensatory mechanisms activated while the bag was being carried, the statistically significant increase in the contact surface at the forefoot (p=.000; 3.6%) and midfoot (p=.000, 8.8%) occurred.
Bibliografija: str. 192-193.
Keywords: Djeca -- Školske torbe -- Pedobarografija -- Biomehanika hoda